2012
DOI: 10.1002/ajhb.22245
|View full text |Cite
|
Sign up to set email alerts
|

Association of PPAR‐γ gene polymorphisms with obesity and obesity‐associated phenotypes in north indian population

Abstract: PPAR-γ gene polymorphisms influence obesity and obesity phenotype in a complex manner, probably involving insulin resistance in north Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 65 publications
(72 reference statements)
1
27
0
Order By: Relevance
“…5 Meanwhile, the Han Chinese from other countries portrayed similar MAF with us, for example the MAF of .25 in Taiwan 29 and .21 in Beijing 30 populations. Similar with our study, this SNP was previously found to have no significant association with obesity [28][29][30][31][32][33][34][35] and Met-S 5,28-30,36 in various populations, while others found positive association with obesity 37,38 and Met-S. 39,40 As with PPARα L162V, this SNP was …”
Section: Discussionsupporting
confidence: 79%
“…5 Meanwhile, the Han Chinese from other countries portrayed similar MAF with us, for example the MAF of .25 in Taiwan 29 and .21 in Beijing 30 populations. Similar with our study, this SNP was previously found to have no significant association with obesity [28][29][30][31][32][33][34][35] and Met-S 5,28-30,36 in various populations, while others found positive association with obesity 37,38 and Met-S. 39,40 As with PPARα L162V, this SNP was …”
Section: Discussionsupporting
confidence: 79%
“…The association between adiponectin concentration and this particular SNP has been reported in a previous study [15]. Moreover, some observational studies have verified the effect of the relationship between the PPARγ Pro12Ala polymorphism and unsaturated fatty acid intake on BMI and WC [7,9].…”
Section: Discussionmentioning
confidence: 97%
“…Treatment with PPARγ agonist drugs, such as thiazolidinediones, causes a two- to threefold increase in the plasma level of adiponectin, along with an improvement in insulin sensitivity in diabetic or insulin-resistant subjects [13,14]. A previous study reported lower values of adiponectin to be associated with the Ala allele of the Pro12Ala polymorphism [15]. …”
Section: Introductionmentioning
confidence: 99%
“…29,33 The absence of replication may be associated with lower coverage of genetic markers in the replication samples as well as different sample sizes. 13 In this vein, our study comes with limitations owing to the small number of participants studied.…”
Section: Pparg-lyplal1 Association With Obesity and Overweight -Hernámentioning
confidence: 99%